Multiplication rate variation in the human malaria parasite Plasmodium falciparum - Lee Murray (Nature Portfolio, 2017)
Abstract It is important to understand intrinsic variation in asexual blood stage multiplication rates of the most virulent human malaria parasite, Plasmodium falciparum. Here, multiplication rates of long-term laboratory adapted parasite clones and new clinical isolates were measured, using a newly standardised assay of growth from low starting density in replicate parallel cultures with erythrocytes from multiple different donors, across multiple cycles. Multiplication rates of long-term established clones were between 7.6 and 10.5 fold per 48 hours, with clone Dd2 having a higher rate than others (clones 3D7, HB3 and D10). Parasite clone-specific growth was then analysed in co-culture assays with all possible heterologous pairwise combinations. This showed that co-culture of different parasites did not affect their replication rates, indicating that there were no suppressive interactions operating between parasites. Multiplication rates of eleven new clinical isolates were measured after a few weeks of culture, and showed a spectrum of replication rates between 2.3 and 6.0 fold per 48 hours, the entire range being lower than for the long-term laboratory adapted clones. Multiplication rate estimates remained stable over time for several isolates tested repeatedly up to three months after culture initiation, indicating considerable persistence of this important trait variation.